A preliminary investigation of the barriers to clean water access in the urban slums of Kolkata, India - Holly Anne Beistline (Health for All Nations, 2016)
Introduction: Safe drinking water is scarce in Kolkata. Inadequate knowledge and poor practices of storing and cleaning drinking water can cause severe effects on the health of the population. There is a need to understand the current trend of attitudes and practices of individuals living in urban slums to reduce water-borne diseases and mortality. This limited convenience sample study attempted to explore and identify areas for further study regarding the barriers of clean water access in urban slums of Kolkata, India. Methods: This pilot cross-sectional study was conducted in Kolkata, India during July 2014. Five urban slums were selected based on proximity and cooperation from the community. A sample of 50 women was taken, representing the five slums, with a sample of 10 women taken from each slum. Results: The majority (80%) of the participants said they regularly have enough water available to meet the needs of their household. Fifty-two percent of subjects received their water for drinking from a tap, hand pump, or time pump. Thirty percent had water pumped into their homes, and 18% purchased their water from a water truck. Fourteen percent said they did not treat their water because it was too time consuming, 40% said it was too much work, and 34% said it was not needed. Ninety percent said they felt it was important to clean their water, almost half (48%) thought their water was not clean, but only 42% used some method to clean their water. Many subjects (68%) stated they knew how to clean their water, but 66% were unaware that visible dirt is not an indicator of illness-causing bacteria in water. Conclusions: More focus should be directed towards improving awareness and knowledge and changing attitudes, motivation, and perceived susceptibility to disease from water within slum communities in Kolkata, India.